Roughage quality determines the production performance of post-weaned Hu sheep via altering ruminal fermentation, morphology, microbiota, and the global methylome landscape of the rumen wall - Ma, Sen; Zhang, Yan; Li, Zidan; Guo, Ming; Liu, Boshuai; Wang, Zhichang; Cui, Yalei; Wang, Chengzhang; Li, Defeng; Shi, Yinghua (Frontiers in Microbiomes, 2024)
Roughage quality is a crucial factor influencing the growth performance and feeding cost of ruminants; however, a systematic investigation of underlying mechanisms is still lacking now. Herein, we examined the growth performance, meat quality, ruminal fermentation parameters, rumen microbiome, and tissue methylomes of post-weaned Hu sheep fed low or high-quality forages-based diets. Our results showed that sheep in alfalfa hay (AG) and peanut vine (PG) groups exhibited better growth performance, slaughter performance, and meat quality than sheep in wheat straw group (WG). Sheep in AG possess relatively higher content of serum immunoglobins (IgA, IgG, and IgM) and lower content of serum inflammation factors (TNF-α, IL-1β, IL-6, IL-8) than animals in WG and PG. Otherwise, the levels of blood T lymphocytes (CD4 + and CD8 + ) and CD4/CD8 ratio are significantly higher in AG than WG and PG.Concentration of ruminal NH3-N is highest in WG; whereas, the concentrations of individual and total SCFAs ranked 1 st in PG. Length, width, and surface area of ruminal papilla markedly differed among three groups, with sheep in PG being the best morphologically developed. Main ruminal microbes at genus level include Prevotella_1, Rikenellaceae_RC9_gut_group, norank_f_F082, Ruminococcus_1, Ruminococcus_2, and other species. Relative abundances of certain species are positively or negatively associated with fermentation parameters and growth index.For example, the fibrolytic bacteria Ruminococcaceae_UGG-001 showed positive relationships with the concentration of SCFAs, except propionate. In addition, the relative abundances of fibrolytic bacterium (e.g., g_Ruminoccus_1) showed negative relationship with starch-degrading bacterium (e.g., g_Prevotellaceae). Genome-wide DNA methylation analysis reveals that rumen tissues in PG and WG occupy differential global DNA methylomes. Genes with differentially methylated promoters involve in known pathways (e.g., FoxO signaling pathway) and GO terms (e.g., anatomical structure morphogenesis) pertaining to rumen development. Two candidate genes (ACADL and ENSOARG00020014533) with hyper-and hypomethylated promoters are screened as potential regulators of rumen development. In conclusion, roughage quality determines sheep growth performance via directly influencing rumen fermentation and microbiome composition, and indirectly affecting rumen development at epigenetic level. influencing ruminal fermentation, microbiota composition, and DNA methylation mediated rumen development.